Factors Related to Altruism among Rescue Volunteers in Disaster Preparedness in Cianjur Regency - Johan Budhiana; Rosliana Dewi; Ady Waluya; Waqid Sanjaya; Yohan Frans Unmehopa (Jurnal Ragam Pengabdian, 2026)
Indonesia is a country with a high level of disaster vulnerability, requiring anticipatory efforts to reduce the impact. In facing theseconditions, volunteers play an important role as the front line in disaster management. Altruistic behavior is the main basis for volunteer  involvement, which in practice is influenced by various factors such as self-efficacy, empathy, and resilience. This study aims to identify factors  related to altruism among rescue volunteers in disaster preparedness. This study uses a correlational cross-sectional approach. The sample consists of 62 people using total sampling. Data were collected using questionnaires and analyzed using Yates' correction. There is a relationship between self-efficacy (p < 0.001), empathy (p < 0.001), and resilience (p 0.009) with altruism among rescue volunteers in disaster preparedness. There is a relationship between self-efficacy, empathy, and resilience with altruism among rescue volunteers in disaster preparedness.